PENGARUH MODAL KERJA TERHADAP RENTABILITAS PADA CV. IFMI MOTOR KOTARAYA - Aswar, Aswar (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of the research are 1) to find out and analyze simultaneous effect of working capital consisting of quantitative working capital, qualitative working capital, and functional working capital on profitability at CV. IFMI Motor Kotaraya. 2) to find out and analyze the partial influence of quantitative working capital on rentability at CV. IFMI Motor Kotaraya. 3) to determine and analyze the partial effect of qualitative working capital on rentability at CV. IFMI Motor Kotaraya. 4) to determine and analyze partial effect of functional working capital on rentability at CV. IFMI Motor Kotaraya. Type of research is causal descriptive. Data analysis technique is path analysis. The results show that: 1) working capital of CV. IFMI Motor Kotaraya during 2012-2016 seen from the quantitative working capital and functional working capital has been decreased every year, while the qualitative working capital showed annual increase. 2) working capital consisting of quantitative working capital, qualitative working capital, and functional working capital simultaneously have significant effect on rentability at CV. IFMI Motor Kotaraya. 3) quantitative working capital partially has a negative and significant effect on profitability at CV. IFMI Motor Kotaraya. 4) qualitative working capital partially has a positive and significant effect on profitability at CV. IFMI Motor Kotaraya. 5) functional working capital partially has positive but non- significant effect on profitability at CV. IFMI Motor Kotaraya.